2022
DOI: 10.1152/physrev.00037.2020
|View full text |Cite
|
Sign up to set email alerts
|

The role of globins in cardiovascular physiology

Abstract: Globin proteins exist in every cell type of the vasculature, from erythrocytes to endothelial cells, vascular smooth muscle cells, and peripheral nerve cells. Many globin subtypes are also expressed in muscle tissues (including cardiac and skeletal muscle), in other organ-specific cell types, and in cells of the central nervous system. The ability of each of these globins to interact with molecular oxygen (O2) and nitric oxide (NO) is preserved across these contexts. Endothelial α-globin is an example of extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 281 publications
1
14
0
Order By: Relevance
“…Following ischemiarelated strain, every molecule which possess the ability to increase oxygen delivery or reduce reactive oxygen species -induced damage is supposed to improve cell survival. In agreement with this, many studies have shown that lowered Ngb amounts in experimental models hindered viability of cultured neuronal cells, whilst amplification of Ngb increased vitality [51,52].…”
Section: Neuroprotective Properties Of Neuroglobinsupporting
confidence: 56%
“…Following ischemiarelated strain, every molecule which possess the ability to increase oxygen delivery or reduce reactive oxygen species -induced damage is supposed to improve cell survival. In agreement with this, many studies have shown that lowered Ngb amounts in experimental models hindered viability of cultured neuronal cells, whilst amplification of Ngb increased vitality [51,52].…”
Section: Neuroprotective Properties Of Neuroglobinsupporting
confidence: 56%
“…Globin proteins in the cells of the vascular wall can regulate vasodilatory NO signaling between endothelium and smooth muscle [ 10 , 11 , 12 , 13 , 14 , 41 , 42 ]. Each globin has unique properties with respect to regulating NO/nitrite/nitrate and O 2 affinity [ 9 ]; however, to provide a continuous reserve of NO scavenging (through dioxygenation, in normoxic conditions) or production (nitrite reductase, in hypoxic conditions), oxidized (Fe 3+ ) globin needs to be recycled to the (Fe 2+ ) globin reduced state. In the myoendothelial junctions (MEJs) of ECs, oxygenated (Fe 2+ ) α-globin bound to eNOS promotes vasoconstriction by degrading locally produced NO to generate NO 3 − and oxidized (Fe 3+ ) α-globin, which is unable to degrade NO further [ 11 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…These globins, particularly cytoglobin, may serve as reversible ligand carriers and may also participate in redox reactions, but their biological functions are currently unclear [ 7 ]. Each member of the globin family of proteins has a distinct pattern of tissue expression, subcellular localization, and affinity for external ligands, including O 2 , carbon dioxide (CO 2 ), and NO [ 8 , 9 ]. Globin proteins in the cells of the vascular wall can regulate vasodilatory NO signaling between endothelium and smooth muscle, inactivating and detoxifying NO by transforming it to nitrate (NO 3 − ) or reducing nitrite (NO 2 − ) to active NO under hypoxic conditions to enable autoregulation of tissue perfusion by smooth muscle [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…While undeniably important, abundant evidence from the study of metalloenzymes has shown that the same PCS environment, such as heme b , can display a variety of different properties from electron transfer to reversible O 2 binding, dioxygen reduction, and small molecule functionalization . As a result, these heme proteins perform a wide range of biological processes, including O 2 transport (globins), cell signaling, electron transfer, and enzymatic activities such as catalases, oxidases, , oxygenases, peroxidases, nitric oxide reductases, and sulfite reductases. Therefore, features of the protein environment beyond the PCS are essential in not only fine-tuning the activities of metalloenzymes but also conferring new activities in otherwise similar systems.…”
Section: Introductionmentioning
confidence: 99%